Designing of Zone Tariff in Integrated Transport Systems - Michal Kohani (Communications - Scientific letters of the University of Zilina, 2013)
When designing a tariff system, there are several possibilities how to design the tariff. One of them is dividing the region into the zones. These zones are usually created by stops in one or more municipalities and the price of travelling between arrival and destination stops is determined by the number of travelled tariff zones by the passenger. There are various approaches how to design prices in such a system. In this article we introduce a mathematical model of the tariff zones design based on counting zones and introducing two approaches for designing prices within this system. We will focus on solving this problem using a universal optimisation tool Xpress, on data set of the selected region. We will compare both approaches in terms of solution quality and computational time.